Peran Teladan Keluarga Berpendidikan Agama Islam dalam Pembentukan Nilai Keagamaan Pada Anak - Ashari, Riyan; Masfufah, Masfufah (Continuous Education: Journal of Science and Research, 2025)
This study aims to examine in greater detail how families with an Islamic educational background contribute to the formation of children’s religious values through consistent exemplary behavior in daily life. By employing a descriptive qualitative approach with a case study method, this research involved three Muslim families residing in Surabaya. Data were collected through in-depth interviews, participatory observation, and documentation to explore how parental behavior influences children's understanding and internalization of Islamic teachings. The study found that consistent parental practices such as performing daily prayers together, demonstrating honesty, patience, and compassion, and engaging in open discussions about religious matters play a crucial role in shaping children's spiritual and moral development. Children tend to imitate religious practices they observe at home, especially when reinforced through positive family communication and emotional support. The findings also show that the synergy between family practices and formal religious education further strengthens the children’s internalization of Islamic values. Parents with Islamic educational backgrounds are shown to have a stronger awareness of the importance of being role models and fostering a religious environment. This study emphasizes the concrete impact of parental consistency and conscious modeling in cultivating faith-based values, highlighting the family’s central role as the first and most influential educational setting for children.